CMOS‐Compatible HfOx‐Based Radiation Hardening Component for Neuromorphic Computing Applications - Yao‐Feng Chang; Yifu Huang; Chin‐Han Chung; Ying‐Chen Chen (Advanced Electronic Materials)
Abstract HfOx‐based resistive random‐access‐memory (ReRAM) devices (TiN/Ti/HfOx/RuOx/TiN) are fabricated by CMOS‐compatible materials (ruthenium (Ru)) and lithography‐lite process, potentially enabling a maskless, etching‐free process that can be implemented in the low earth orbit (LEO), the International Space Station (ISS), and commercial LEO destinations (CLDs). The devices met the requirements for qualified manufacturers list verification (QMLV) and radiation hardness assurance (QMLV‐RHA), as well as Advanced Next Generation Strategic Radiation, hardened Memory (ANGSTRM), which potentially support LEO, medium earth orbit, and geosynchronous orbit missions. Specifically, after a 5‐Mrad total ionizing dose (TID) test, the electrical characterized results showed non‐degradation performance, memory window ≈40 with operation power <   mW, capability of >  000‐times endurance and 15‐year retention. The Ruthenium oxide (RuOx) can serve as a photon‐absorb sink to reduce the switching layer damage caused by heating induced by radiation, supported by Particle and Heavy Ion Transport Code System Monte Carlo simulation. Furthermore, the neural network by HfOx/RuOx‐based ReRAM device is trained with the inference accuracy at various TIDs for a potential neuromorphic hardware system demonstration. The results show that HfOx/RuOx‐based ReRAM neuromorphic computing is quite robust as a radiation‐hardened structure, providing a development path to realize programmable computing chip tolerance under irradiation.